2015
DOI: 10.1016/j.juro.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone Resistance in the Rectal Carriage of Men in an Active Surveillance Cohort: Longitudinal Analysis

Abstract: Purpose Rectal swabs can identify men with fluoroquinolone resistant bacteria and decrease the infection rate after transrectal ultrasound guided prostate biopsy by targeted antimicrobial prophylaxis. We evaluated the rate of fluoroquinolone resistance in an active surveillance cohort with attention to factors associated with resistance and changes in resistance with time. Materials and Methods We evaluated 416 men with prostate cancer on active surveillance who underwent rectal swabs to assess the rate of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…Any potential risk is concerning in this context, with a retrospective analysis reported increased odds of an infection (OR 1.33, 95%CI 1.01 -1.74) for every previous biopsy in 591 consecutive men undergoing TRUBP 77 . Repeat biopsy has been reported to be a risk factor for colonisation with resistant E. coli strains 78 , with a progressive increase reported for each biopsy undertaken 79 . Post-biopsy complications have been reported to reduce rates of repeat biopsy in men undergoing active surveillance 80 .…”
Section: Previous Biopsiesmentioning
confidence: 99%
“…Any potential risk is concerning in this context, with a retrospective analysis reported increased odds of an infection (OR 1.33, 95%CI 1.01 -1.74) for every previous biopsy in 591 consecutive men undergoing TRUBP 77 . Repeat biopsy has been reported to be a risk factor for colonisation with resistant E. coli strains 78 , with a progressive increase reported for each biopsy undertaken 79 . Post-biopsy complications have been reported to reduce rates of repeat biopsy in men undergoing active surveillance 80 .…”
Section: Previous Biopsiesmentioning
confidence: 99%
“…Infectious complications were particularly common in our series despite antibi- had been taken in advance, but diabetes is currently considered to be one of the risk factors for quinolone resistance [12]. Antibiotic prophylaxis adapted to the result of rectal swab sampling would reduce the risk of infection [13].…”
Section: Infectious Complicationsmentioning
confidence: 81%
“…This rise in rates of TRPB‐related infection has been paralleled with the dramatic increase in fluoroquinolone‐resistant organisms . Recent studies have reported that up to one‐fourth of men undergoing prostate biopsy are colonized with rectal flora demonstrating fluoroquinolone resistance . It is therefore not surprising that higher rates of infection have been attributed to increasing antibiotic resistance and in particular increasing resistance to fluoroquinolones.…”
Section: Introductionmentioning
confidence: 99%